2016
DOI: 10.1186/s13014-015-0578-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological impact of dose calculation algorithms on biologically optimized IMRT lung stereotactic body radiation therapy plans

Abstract: BackgroundThe aim of this study is to evaluate the radiobiological impact of Acuros XB (AXB) vs. Anisotropic Analytic Algorithm (AAA) dose calculation algorithms in combined dose-volume and biological optimized IMRT plans of SBRT treatments for non-small-cell lung cancer (NSCLC) patients.MethodsTwenty eight patients with NSCLC previously treated SBRT were re-planned using Varian Eclipse (V11) with combined dose-volume and biological optimization IMRT sliding window technique. The total dose prescribed to the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
2
27
1
Order By: Relevance
“…Recently, biological constraints, such as generalized equivalent uniform dose (gEUD), tumor control probability (TCP) and normal tissue complication probability (NTCP), have been used in IMRT planning process [4]. Biological parameters, which applied in biological models to predict the biological effect of tumor and normal tissues, have more direct correlation with treatment outcome than physical parameters [510]. Research shows that, with similar target coverage, biological optimization could spare more organs at risk (OARs) than physical optimization [1118].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biological constraints, such as generalized equivalent uniform dose (gEUD), tumor control probability (TCP) and normal tissue complication probability (NTCP), have been used in IMRT planning process [4]. Biological parameters, which applied in biological models to predict the biological effect of tumor and normal tissues, have more direct correlation with treatment outcome than physical parameters [510]. Research shows that, with similar target coverage, biological optimization could spare more organs at risk (OARs) than physical optimization [1118].…”
Section: Introductionmentioning
confidence: 99%
“…It should be stated that there are large uncertainties in the currently used biological models and associated parameters, so the application of results from conventional to SBRT approach ( 56 ) or from a dose algorithms to another ( 57 ) should be performed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies showed that AAA overestimates the PTV dose and TCP compared to Acuros-XB using Poisson model with LQ. The difference can be reached up to 5.8% for TCP, while both algorithms yield very similar normal tissue complication probability (NTCP) on lung pneumonitis based on the LKB model parameter (28,29). However, the more advanced algorithms such as AAA, Acrous-XB, collapsed cone and MC would be recommended to better calculate the dose for tumor and to avoid the over/under estimating TCP/NTCP outcome.…”
Section: Precaution To Use Tcp In Order To Rank and Optimize Radiothementioning
confidence: 99%